St. Vincent and The Grenadines : Staff Report for the 2000 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2000)
The government of St. Vincent and the Grenadines has launched an economic diversification program in the mid-1990s and strengthened measures to deal with the decline in the banana sector, which has been the economy's mainstay for several decades. Reflecting some success from these efforts, real gross domestic product growth-which has averaged 2 1\2 percent a year during 1993-97 with significant volatility-has surged to 5 percent a year during 1998-99. The last census in 1991 has estimated the unemployment rate at 19 percent.